2011
DOI: 10.1021/bi200027v
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Heme Orientation and Binding by a Single Residue in Catalase HPII of Escherichia coli

Abstract: Heme-containing catalases have been extensively studied, revealing the roles of many residues, the existence of two heme orientations, flipped 180° relative to one another along the propionate-vinyl axis, and the presence of both heme b and heme d. The focus of this report is a residue, situated adjacent to the vinyl groups of the heme at the entrance of the lateral channel, with an unusual main chain geometry that is conserved in all catalase structures so far determined. In Escherichia coli catalase HPII, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…This model is one of the most complete protein models in the PDB examined so far (Table I), and has the smallest R-factor gap with R Ratio of 1.22 (see Methods). [4][5][6][7][8][9][10][11][12][13][14][15] Evidence will be provided below that its corresponding residual ED map is the closest to true featurelessness with all the residual peaks contributed mainly by random noise present in the intensity data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model is one of the most complete protein models in the PDB examined so far (Table I), and has the smallest R-factor gap with R Ratio of 1.22 (see Methods). [4][5][6][7][8][9][10][11][12][13][14][15] Evidence will be provided below that its corresponding residual ED map is the closest to true featurelessness with all the residual peaks contributed mainly by random noise present in the intensity data.…”
Section: Resultsmentioning
confidence: 99%
“…17 A few are selected here for this analysis ( Table I). [4][5][6][7][8][9][10][11][12][13][14][15] It is shown that the 5BV2 model 4 appears to be the only one whose intensity differences between the model and data are truly limited by random noise present in the diffraction data (see below).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, the heme is present with equal proportions of two orientations flipped relative to one another. All clade 3 enzymes so far characterized have one orientation of heme while a clade 1 enzyme (CatF of Pseudomonas syringae ) has predominantly the flipped orientation similar to that in the large subunit KatE from E. coli . It is perhaps relevant that changing the residues adjacent to the heme in KatE did influence the heme orientation leading to mixtures .…”
Section: Resultsmentioning
confidence: 99%
“…Only five different amino acids are found at the location among all catalases, including Val (62%), Ser (32%), Gly (3%), Ile (2%), and Ala (1%) (Jha et al, 2011). To investigate the integrity of this residue in the catalytic function of the enzyme, it was mutated to residues found at the same location in other catalases.…”
Section: Characterization Of Catpo Variantsmentioning
confidence: 99%
“…Thus, the bulky valine or isoleucine restricts movement of H 2 O 2 out of the cavity via the lateral channel, and the longer occupancy in the cavity increases its chances of participating in the reaction. Conversely, opening the lateral channel (with smaller side chains at residue 228) facilitates diffusion of H 2 O 2 out of the cavity, leading to a shorter residency time, poorer substrate binding, and a slower reaction (Jha et al, 2011).…”
Section: Characterization Of Catpo Variantsmentioning
confidence: 99%